Marginality in the context of the new rurality: application to the case of Malargüe in Mendoza, Argentina - Cepparo, María Eugenia

(untitled)
In Malargüe, the southernmost department of the province of Mendoza, two different rural realities coexist: a small area with intensive farming around the urban centre, and a larger area where goat-grazing prevails. Whereas structural problems continue to affect extensive and transhumant cattle raising in the most fragile areas of the territory, in recent years the intensive agricultural development of vegetables, forestry and fodder has grown in the peri-urban area. From the perspective of the theoretical framework of marginality, both areas have different relations to the processes that characterise marginality. This was one of the ideas that guided the study of the rural area of the department. UGI, Barcelona.